Ethnicity and social capital among the urban middle class in Kuala Lumpur, Malaysia / Aliye Nur Kelesoglu - Aliye Nur , Kelesoglu (2019)

(untitled)
This study investigates the relationship between the low level of social capital and ethnic diversity in Kuala Lumpur, Malaysia. Its aim is to understand the underlying reasons for the low level of social capital and its relation to the ethnic diversity, focusing on the problems of ethnic Malay, Chinese and Indian Malaysians in building and maintaining social connections with each other. According to the results of the World Values Survey (2014) and the Asian Barometer Survey (2016), distrust among Malaysians is common, while shared values and norms are rare, and they are not eager to actively participate in civic life. The research problem was investigated in three parts. In the first part, the dynamics of building social capital and meaningful contact between nonethnics – namely, bridging social capital of the participants – were examined. The second part investigated inter-ethnic problems at the individual level causing a low level of social capital in Malaysia. In the last part, by focusing on the societal level, the impact of government implementations and state policies on non-ethnic relationships and building social capital was analysed. For this research, qualitative methodology was preferred, and 21 in-depth interviews were conducted. Each ethnic group was represented by seven participants. All participants belonged to the middle class, from the three main ethnic groups – Chinese, Indian and Malay – and were professionals living in Kuala Lumpur, Malaysia. The primary reason for choosing Kuala Lumpur as the research area was its multi-ethnic and multi-religious nature. In this regard, the city offers a unique sample characteristic across Malaysia. Key research findings point, firstly, to the fact that the Indian participants were the most willing to trust and make contact with other Malaysians compared with the Chinese and Malay participants, which demonstrates that if the ethnic group size is relatively smaller than out-groups, group members have more opportunity to interact with out-group members. Meaningful contact is also crucial in the creation of trust relationships and bonds between non-ethnics. Secondly, even though meaningful intergroup contact can create positive feelings between non-ethnics, a lack of acceptance or tolerance, less exposure to other cultures, and misunderstandings or a lack of understanding between non-ethnics undermined the beneficial impacts of intergroup contacts, social trust and social capital. Lastly, it was found at the societal level that the feeling of discrimination, ethnicity-based political system, nationalist discourse promoting fear of other races, and the high in-group solidarity of the Chinese reinforced bonding social capital and eradicated intergroup trust while promoting the perceived threat of non-ethnics towards each other.